Manajemen Transportasi Cerdas BRT Jakarta - Mohammad Jafar Loilatu; Dian Eka Rahmawat; David Efendi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
This study aims to look at the factors that drive the Jakarta BRT public transportation to be of interest. This research method uses qualitative methods, data sources in this study include (satudatajakarta.com), (transjakarta.com) and (opendata.com), this study also uses the qualitative data analysis software (QDSA) NVivo 12 plus method. The results of this study answer the increase in the number of TransJakarta users driven by the number of modern infrastructure and integrated transportation systems. Management of information through social media, websites, and applications encourages the quality of TransJakarta services, trans-Jakarta users can access information quickly about location and information on Transjakarta. Keywords: Transjakarta, BRT, Management, Infrastructure.